Dynamic Associations among Somatic Complaints, Human Energy, and Discretionary Behaviors - Christian, Michael S.; Eisenkraft, Noah; Kapadia, Chaitali (Administrative Science Quarterly, 2015)
Using data from two experience-sampling studies, this paper investigates the dynamic relationships between discretionary behaviors at work—voluntary tasks that employees perform—and internal somatic complaints, focusing specifically on a person’s pain fluctuations. Integrating theories of human energy with evidence from the organizational, psychological, and medical sciences, we argue that pain both depletes and redirects the allocation of employees’ energy. We hypothesize that somatic pain is associated with depleted resources and lowered work engagement, which in turn are related to ebbs and flows in discretionary behaviors, but that people will habituate to the negative effects of pain over time. Data from the two studies largely support our hypotheses. Study 1 explores the daily experiences of a sample of office workers with chronic pain, while Study 2 extends the findings to a larger non-clinical population and examines the effect of momentary pain during the workday. Our results suggest that pain fluctuations, through their effects on two forms of human energy, potential and in-use energy, are associated with increased withdrawal and a decrease in proactive extra-role behaviors at work. The results also suggest that employees who have experienced chronic pain for a longer time are less affected by the normally depleting effects of pain.